Groundwater Survey Using Resistivity Method for Drought Mitigation in Bima Regency, West Nusa Tenggara - Prabowo, Adi; Hartono, Hartono; Kaeni, Oscar (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Groundwater Survey in Bolo District, Palibelo District, Woha District, Langgudu District, Wawo District, Sape District, Wera District, Bima Regency, and West Nusa Tenggara for drought mitigation has been implemented. The study area is located in the majority of hilly areas with soil vulnerable to drought. Water is abundant during the rainy season. However, during the dry season, the ground surface is cracked, and there needs to be more clean water. This situation is troubling the community and the Regional Government of Bima Regency. The study was conducted using the Schlumberger resistivity geoelectric configuration method. The measurement point is in seven sub-districts, with a total of 18 measurement points. Research location at 118,6305833 SL; -8,3008888889 EL up to 119,01925 SL; -8,704638889 EL or covers an area of ± 1,961 km2. The length of the path used is a maximum of 400 meters. Based on the results of geoelectric resistivity data, two types of aquifers are found, open aquifers with depths ranging from 1 m to 26 m and aquifers depressed with depths ranging from 70 to 115 m. In addition to geoelectric information data, drilling data is also used at points that can be reached by heavy equipment in Lanta Barat Village, Lambu District. At the drilling point, the presence of an aquifer layer is obtained at a depth of about 80 meters. Residents then use the discovery of the wellbore to meet their need for clean water.